2016
DOI: 10.36834/cmej.36772
|View full text |Cite
|
Sign up to set email alerts
|

Physician recruitment and retention in New Brunswick: a medical student perspective

Abstract: Background: Physician recruitment and retention is a priority for many Canadian provinces. Each province is unique in terms of recruitment strategies and packages offered; however, little is known about how medical students evaluate these programs. The purpose of the current study was to determine which factors matter most to New Brunswick (NB) medical students when considering their location of future practice.Method: A survey of NB medical students was conducted. Descriptive statistics were produced and a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Another inconsistency may also be due to the sample size of doctors in our study considering marriage. Spousal influence is considered to play a significant role in the recruitment and retention of physicians, as shown in previous studies (Cameron et al, 2012;Giberson et al, 2016;Russell et al, 2018;Levesque et al, 2018). We observed that significant differences in the anticipated retention rate were introduced because of marriage in univariate analysis, but they failed to affect the binary logistic regression model.…”
Section: Discussionsupporting
confidence: 64%
“…Another inconsistency may also be due to the sample size of doctors in our study considering marriage. Spousal influence is considered to play a significant role in the recruitment and retention of physicians, as shown in previous studies (Cameron et al, 2012;Giberson et al, 2016;Russell et al, 2018;Levesque et al, 2018). We observed that significant differences in the anticipated retention rate were introduced because of marriage in univariate analysis, but they failed to affect the binary logistic regression model.…”
Section: Discussionsupporting
confidence: 64%
“…8 The direct effect included operating expenditures (salaries and benefits, travel, supplies and services, stipends paid to preceptors, student spending, and research expenditure) and excluded capital expenditures. These numbers were considerably lower than the 2.5 used by Tripp and Umbach 5 in their Canada-wide study of medical programs but are similar to Sudmant’s multiplier of 1.5. 36 The impact of the Saguenay DME program was estimated in terms of its impact on local income revenue and total employment following the NOSM method.…”
Section: Resultsmentioning
confidence: 48%
“…1 , 2 Increasing the training opportunities for medical doctors outside of large urban centres reduces the disparity in medical services between rural and urban areas. 3 - 5 Medical school graduates are more likely to remain in the region where they trained. 6 Hence, the development of training opportunities in underserved areas mitigates the shortage of physicians.…”
Section: Introductionmentioning
confidence: 99%
“…This historical aspect is difficult to capture retrospectively but represents a potential confounder. Moreover, this study relied on administrative data, which did not capture a wide range of factors that may have affected decision making about work locations, such as a spouse’s ability to work in the region 16 . The identification of practice location of participants at a single point in time is another limitation of the study.…”
Section: Discussionmentioning
confidence: 99%